From simulation to sustainability: using forest growth models for indicator-based bioeconomy monitoring - Mirjam Pfeiffer; Rüdiger Grote; Joachim Rock; Mart-Jan Schelhaas; Andreas Huth; Sara Filipek; Christopher P. O. Reyer; Boris Sakschewski; Sarah Bereswill; Mats Nieberg; Jessica Hetzer; Tim Anders; et al. (Regional Environmental Change, 2026)

Alternative training methods in soccer - Stefanie Klatt; Lukas Thönnißen; Tim Fischer; Anton Sandmann (German Journal of Exercise and Sport Research, 2026)
The increasing level of physical fitness among soccer players necessitates the exploration of alternative training methods to enhance overall performance. Perceptual–cognitive skills are crucial for sport-specific capabilities such as decision making and reactive agility, enabling athletes to extract visual information from foveal, parafoveal, and peripheral vision. This study focuses on optimizing the utilization of peripheral vision in sports, addressing the demand for specialized training techniques and investigating additional avenues for practicing soccer-specific skills. This study assessed the impact of a 6-week intervention on the perceptual–cognitive performance of elite youth soccer players by examining peripheral perception, response time, and task-switching during soccer-specific motion execution. Outcomes were measured through a reactive agility test, a simulated decision-making task, and a maximal sprinting speed test. Using a pre–post design, 22 healthy male participants were divided into an experimental group and an active control group. The experimental group engaged in sport-specific tasks designed to enhance their perceptual–cognitive skills. Results revealed that the experimental group demonstrated significant improvements in reaction time during both the reactive agility test with and without a ball, an increase in the number of correct decisions in the simulated decision-making task, and a noteworthy enhancement in maximum sprinting speed, while handling a ball compared to the control group. While further research is needed to translate these findings into practical field settings, this study indicates that soccer-specific demands, extending beyond physical aspects, can be effectively targeted and improved.

Plant vs Dairy protein stabilised cappuccino foams: how protein and hydrocolloid conformational changes affect foam stability - Silvana Wüest; Johann Buczkowski; Nykola C. Jones; Søren Vrønning Hoffmann; Peter Fischer; Tim J. Wooster (Food Hydrocolloids, 2025)

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Linking physical processes to biological responses: Interdisciplinary observational insights into the enhanced biological productivity of the Cape Verde Archipelago - Florian Schütte; Anna Christina Hans; Marco Schulz; Rebecca Hummels; Olivier Assokpa; Peter Brandt; Rainer Kiko; Arne Körtzinger; Björn Fiedler; Tim Fischer; Elizandro Rodrigues; Henk-Jan Hoving; et al. (Progress in Oceanography, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Mesoscale cyclonic eddies born in an eastern boundary upwelling system enhance microbial eukaryote diversity in oligotrophic offshore waters - Sven Nicolai Katzenmeier; Maren Nothof; Hans-Werner Breiner; Tim Fischer; Thorsten Stoeck (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

FAIR ADCP data with OSADCP: a workflow to process ocean current data from vessel-mounted ADCPs - Robert Kopte; Marius Becker; Tim Fischer; Peter Brandt; Gerd Krahmann; Maximilian Betz; Claas Faber; Christian Winter; Johannes Karstensen; Gauvain Wiemer (Frontiers in Marine Science, 2024)
This paper presents the open-source Python software OSADCP developed for the processing of vessel-mounted Acoustic Doppler Current Profiler (VMADCP) data. At this stage, the toolbox is designed for processing VMADCP measurements from open-ocean applications of Teledyne RDI Ocean Surveyor ADCPs and the data acquisition software VMDAS . Based on the VMDAS ENX binary output format, the software contains implementations for cleaning and vector-averaging of single-ping velocity data, verification of the position data, and applying misalignment and amplitude corrections. The procedures of OSADCP are described in detail to encourage the scientific community to use it for their own purposes. The toolbox is an integral part of a workflow implemented on the German marine research vessels in the framework of the Underway Research Data project of the German Marine Research Alliance (DAM). It aims to ensure standardized data acquisition measures, reliable data transfer from the ADCP to shore both near-real-time and in delayed-mode, processing and quality control, and dissemination of the curated data product in the data repository PANGAEA . From PANGAEA , data sets are forwarded to the European marine data hubs Copernicus Marine Service and EMODnet . The workflow that forms the framework for OSADCP is described here as an example of scientific data management that follows the FAIR data guidelines.

Behavior of addax (Addax nasomaculatus) and Arabian oryx (Oryx leucoryx) mothers and calves during the calves’ first day of life - Karen L. Bauman; Cheryl S. Asa; Martha Fischer; Tim Thier; William Houston (Applied Animal Behaviour Science, 2023)

Earth Observation for agricultural drought monitoring in the Pannonian Basin (southeastern Europe): current state and future directions - Laura Crocetti; Matthias Forkel; Milan Fischer; František Jurečka; Aleš Grlj; Andreas Salentinig; Miroslav Trnka; Martha Anderson; Wai-Tim Ng; Žiga Kokalj; Andreea Bucur; Wouter Dorigo (Regional Environmental Change, 2020)
The Pannonian Basin in southeastern Europe is heavily used for rain-fed agriculture. The region experienced several droughts in the last years, causing major yield losses. Ongoing climate change, characterised by increasing temperatures and potential evapotranspiration, and by changes in precipitation distribution will likely increase the frequency and intensity of drought episodes in the future. Hence, ongoing monitoring of droughts and estimation of their impact on agriculture is necessary to adapt agricultural practices to changing weather and climate extremes. Several regional initiatives, projects and online tools have been established to facilitate drought monitoring and management in the Pannonian Basin. However, reliable systems to forecast potential drought impacts on plant productivity and agricultural yields at monthly to seasonal scales are only in their infancy, as plant response to climatic extremes is still poorly understood. With the increasing availability of high-resolution and long-term Earth Observation (EO) data and recent progress in machine learning and artificial intelligence, further improvements in drought monitoring and impact prediction capacities are expected. Here we review the current state of drought monitoring in the Pannonian Basin, identify EO-based variables to potentially improve regional drought impact monitoring and outline future perspectives for seasonal forecasts of drought impacts on agriculture.

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

The influence of dissolved organic matter on the marine production of carbonyl sulfide (OCS) and carbon disulfide (CS 2 ) in the Peruvian upwelling - Sinikka T. Lennartz; Marc von Hobe; Dennis Booge; Henry C. Bittig; Tim Fischer; Rafael Gonçalves-Araujo; Kerstin B. Ksionzek; Boris P. Koch; Astrid Bracher; Rüdiger Röttgers; Birgit Quack; Christa A. Marandino (Ocean Science, 2019)
Oceanic emissions of the climate-relevant trace gases carbonyl sulfide (OCS) and carbon disulfide (CS2) are a major source to their atmospheric budget. Their current and future emission estimates are still uncertain due to incomplete process understanding and therefore inexact quantification across different biogeochemical regimes. Here we present the first concurrent measurements of both gases together with related fractions of the dissolved organic matter (DOM) pool, i.e., solid-phase extractable dissolved organic sulfur (DOSSPE, n=24, 0.16±0.04 µmol L−1), chromophoric (CDOM, n=76, 0.152±0.03), and fluorescent dissolved organic matter (FDOM, n=35), from the Peruvian upwelling region (Guayaquil, Ecuador to Antofagasta, Chile, October 2015). OCS was measured continuously with an equilibrator connected to an off-axis integrated cavity output spectrometer at the surface (29.8±19.8 pmol L−1) and at four profiles ranging down to 136 m. CS2 was measured at the surface (n=143, 17.8±9.0 pmol L−1) and below, ranging down to 1000 m (24 profiles). These observations were used to estimate in situ production rates and identify their drivers. We find different limiting factors of marine photoproduction: while OCS production is limited by the humic-like DOM fraction that can act as a photosensitizer, high CS2 production coincides with high DOSSPE concentration. Quantifying OCS photoproduction using a specific humic-like FDOM component as proxy, together with an updated parameterization for dark production, improves agreement with observations in a 1-D biogeochemical model. Our results will help to better predict oceanic concentrations and emissions of both gases on regional and, potentially, global scales.

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Observed El Niño conditions in the eastern tropical Pacific in October 2015 - Lothar Stramma; Tim Fischer; Damian S. Grundle; Gerd Krahmann; Hermann W. Bange; Christa A. Marandino (Ocean Science, 2016)
A strong El Niño developed in early 2015. Measurements from a research cruise on the R/V Sonne in October 2015 near the Equator east of the Galapagos Islands and off the shelf of Peru are used to investigate changes related to El Niño in the upper ocean in comparison with earlier cruises in this region. At the Equator at 85°30′ W, a clear temperature increase leading to lower densities in the upper 350 m had developed in October 2015, despite a concurrent salinity increase from 40 to 350 m. Lower nutrient concentrations were also present in the upper 200 m, and higher oxygen concentrations were observed between 40 and 130 m. In the equatorial current field, the Equatorial Undercurrent (EUC) east of the Galapagos Islands almost disappeared in October 2015, with a transport of only 0.02 Sv in the equatorial channel between 1° S and 1° N, and a weak current band of 0.78 Sv located between 1 and 2°30′ S. Such near-disappearances of the EUC in the eastern Pacific seem to occur only during strong El Niño events. Off the Peruvian shelf at ∼ 9° S, characteristics of upwelling were different as warm, saline, and oxygen-rich water was upwelled. At ∼ 12, ∼ 14, and ∼ 16° S, the upwelling of cold, low-salinity, and oxygen-poor water was still active at the easternmost stations of these three sections, while further west on these sections a transition to El Niño conditions appeared. Although from early 2015 the El Niño was strong, the October measurements in the eastern tropical Pacific only showed developing El Niño water mass distributions. In particular, the oxygen distribution indicated the ongoing transition from “typical” to El Niño conditions progressing southward along the Peruvian shelf.

Ecological fits, mis-fits and lotteries involving insect herbivores on the invasive plant, Bunias orientalis - Jeffrey A. Harvey; Arjen Biere; Taiadjana Fortuna; Louise E. M. Vet; Tim Engelkes; Elly Morriën; Rieta Gols; Koen Verhoeven; Heiko Vogel; Mirka Macel; Hanna M. Heidel-Fischer; Katharina Schramm; et al. (Biological Invasions, 2010)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)